Marking the religious new year - Richardson, Betsy (Richardson, Betsy. Celebrating holidays & festivals around the world., 2019)
Examines various festivals around the world that celebrate a religious new year. Highlights the origins of such celebrations and the traditions associated with them. Includes text-related questions, research projects, a glossary, resources for further information, and color photographs.